Carbonic metamorphism at ultrahigh-temperatures: Evidence from North China Craton - Santosh, M.; Tsunogae, T.; Ohyama, H.; Sato, K.; Li, J. H.; Liu, S. J. (Earth and Planetary Science Letters, 2008)
The North China Craton (NCC) constitutes one of the fundamental Precambrian nuclei of Asia. The Paleoproterozoic khondalite belt along the northern margin of the NCC shows evidence for extreme crustal metamorphism at temperatures exceeding 1000 degrees C and pressures of 10-12 kbar with the formation of diagnostic ultrahigh-temperature (UHT) mineral assemblages including sapphirine + quartz, high alumina orthopyroxene + sillimanite and high-temperature mesoperthites. Here we record for the first time the common occurrence Of CO2-rich fluid inclusions in peak UHT minerals in the Mg-Al granulites of NCC, and trace the fluid evolution history. From microthermometric and laser Raman spectroscopic studies, we show that the syn-metamorphic fluid in the UHT rocks was pure CO2- While very high density carbonic fluids are preserved in some cases, corresponding to entrapment at peak conditions, many of the inclusions underwent density modification during the rapid and near-isothermal exhumation of the rocks following peak LET metamorphism and initial cooling at depth. The present study area within the northern margin of the NCC defines a collisional orogenic belt where continental collision and deep subduction were possibly followed by extensional collapse of the orogen. Evidence for the extensional phase is provided by the several mafic magmatic intrusions of Paleoproterozoic age that are seen emplaced within the granulite facies supracrustals. The thermal anomaly displayed by the UHT granulites may thus correlate with asthenospheric upwelling and emplacement of mafic magmas, possibly associated with plume activity, which provided the heat and CO2 input to achieve extreme crustal metamorphism and generation of dry granulite facies assemblages. Our study is the first report of syn-metamorphic CO2-rich fluids in UHT granulites from a Paleoproterozoic (ca. 1.92 Ga) terrane and provide evidence for carbonic metamorphism at ultrabigh-temperatures as North China Craton joined the Columbia supercontinent amalgam. (c) 2007 Elsevier B.V. All rights reserved. Geochemistry & Geophysics SCI(E) EI 70 ARTICLE 1-2 149-165 266